The diagnostic accuracy of pooled testing from multiple individuals for the detection of Chlamydia trachomatis and Neisseria gonorrhoeae: a systematic review. (May 2022) - Xu, Yangqi; Aboud, Lily; Chow, Eric P.F.; Mello, Maeve B.; Wi, Teodora; Baggaley, Rachel; Fairley, Christopher K.; Peeling, Rosanna; Ong, Jason J.
Highlights: Molecular testing for chlamydia and gonorrhoea is recommended. Molecular testing is expensive and is inaccessible in many resource-limited settings. Single anatomic site pooled testing is a highly sensitive and specific method. Pooled testing could offer significant cost-saving benefits in resource-limited settings. ABSTRACT: Objectives: Molecular testing for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) is costly. Therefore, we appraised the evidence regarding pooling samples from multiple individuals to test for CT/NG. Methods: In this systematic review, we searched 5 databases (2000-2021). Studies were included if they contained primary data describing pooled testing. We calculated the pooled sensitivities and specificities for CT and NG using a bivariate mixed-effects logistic regression model. Results: We included 22 studies: most were conducted in high-income countries (81.8%, 18 of 22), among women (73.3%, 17 of 22), and pooled urine samples (63.6%, 14 of 22). Eighteen studies provided 25 estimates for the meta-analysis of diagnostic accuracy, with data from 6, 913 pooled specimens. The pooled sensitivity for CT was 98.4% (95% confidence intervals [CI]: 96.8-99.2%, I 2 =77.5, p<0.001), and pooled specificity was 99.9% (95% CI: 99.6-100.0%, I 2 =62.6, p<0.001). Only 2 studies reported pooled testing for NG, and both reported similarly high sensitivity and specificity as for CT. Sixteen studies provided data on the cost of pooling, reporting cost-savings ranging from 39%-90%. Conclusions: Pooled testing from multiple individuals for CT is highly sensitive and specific compared with individual testing. This approach has the potential to reduce the cost of screening in populations for which single anatomic site screening is recommended.